Occurrence and deformation of clastic dykes in the Ukrainian Carpathian - Alokhin, V.I.; Bubniak, I.M.; Bihun, M.V. (Geofizicheskiy Zhurnal, 2025)
The study presents the results of research on the occurrence, composition, and deformation features of clastic dykes in the Ukrainian Carpathians. The stratigraphic units of the sedimentary sequence containing clastic dykes, the irgenetic type, morphological features, andmineral-petrographic composition have been identified. Based on field measurements of the orientation elements of dykes and their deformation structures, the systems of dykes and the systems of brittle deformations disrupting their original state have been identified. Based on field measurements of deformation structures using the «Win-Tensor» program, a reconstruction of paleostress fields, with in which the deformations occurred, was performed. The research results indicate that most clastic dykes are of the injection type and were formed under marine conditions. The deformations of these dykes are associated with the formation process of the Folded Carpathians and occurred din multiple stages within stress fields of different kinematic types. Dykes often contain accumulations of organic matter, which makes them useful for assessing the potential of subsurface deposits.